Gene of the month: TMPRSS2 (transmembrane serine protease 2). Issue 12 (1st September 2020) - Thunders, Michelle; Delahunt, Brett
Abstract : Transmembrane serine protease 2 is encoded by the TMPRSS2 gene. The gene is widely conserved and has two isoforms, both being autocatalytically activated from the inactive zymogen form. A fusion gene between the TMPRSS2 gene and ERG (erythroblast-specific-related gene), an oncogenic transcription factor, is the most common chromosomal aberration detected in prostate cancer, responsible for driving carcinogenesis. The other key role of TMPRSS2 is in priming the viral spike protein which facilitates viral entry essential for viral infectivity. The protease activates a diverse range of viruses. Both SARS-CoV and SARS-CoV-2 (COVID-19) use angiotensin-converting enzyme 2 (ACE2) and TMPRSS2 to facilitate entry to cells, but with SARS-CoV-2 human-to-human transmission is much higher than SARS-CoV. As TMPRSS2 is expressed outside of the lung, and can therefore contribute to extrapulmonary spread of viruses, it warrants further exploration as a potential target for limiting viral spread and infectivity.